THE ROLE OF THE DISCUSSION TYPE OF SPEECH IN THE LANGUAGE SYSTEM (Scientific journal of the Fergana State University, 2025)
The language consists of two interconnected subsystems: functional-semantic and normative-stylistic systems. The first is characterized by its recurring stable typical features and mutual conditioning. The normative-stylistic subsystem, on the contrary, does not have such stable features. This noted systemic nature of the language is more clearly manifested in a comparative analysis of speech styles.